Cholinergic Pathway SNPs and Postural Control in 477 Older Adults - Arnold, Carina; Schulte, Claudia; Moscovich, Mariana; Sünkel, Ulrike; Zaunbrecher, Laura; Metzger, Florian; Gasser, Thomas; Eschweiler, Gerhard W.; Hauser, Ann-Kathrin; Berg, Daniela; Maetzler, Walter (Frontiers in Aging Neuroscience, 2018)
Objective: To determine whether single nucleotide polymorphisms (SNPs) of the cholinergic system and quantitative parameters of postural control are associated in healthy older adults. This is a cross-sectional analysis from the TREND study. Methods: All participants performed a static postural control task for 30 s on a foam pad in semitandem stance and eyes closed. We analyzed mean power frequency (MPF), area, acceleration, jerk, and velocity from a mobile sensor worn at the lower back using a validated algorithm. Genotypes of four SNPs in genes involved in the cholinergic system (SLC5A7, CHAT, BCHE, CHRNA4) were extracted from the NeuroX chip. All participants present a normal neurological examination and a Minimental state examination score >24. Results: Four hundred and seventy seven participants were included. Mean age was 69 years, 41% were female. One SNP of the cholinergic pathway was significantly associated with a quantitative postural control parameter. The minor allele of rs6542746 in SLC5A7 was associated with lower MPF (4.04 vs. 4.22 Hz; p = 3.91 × 10-4). Moreover, the following associations showed trends toward significance: minor allele of rs6542746 in SLC5A7 with higher anteroposterior acceleration (318 vs. 287 mG; p = 0.005), and minor allele of rs3810950 in CHAT with higher mediolateral acceleration [1.77 vs. 1.65 log(mG); p = 0.03] and velocity [1.83 vs. 1.74 log(mm/s); p = 0.019]. Intraindividual occurrence of rs6542746 and rs3810950 minor alleles was dose-dependently related with lower MPF (p = 0.004). Conclusion: This observational study suggests an influence of SNPs of the cholinergic pathway on postural control in older adults.